(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
The contribution focuses on pretend play, a kind of play that is found in children of all cultures and is easily recognizable by adults. The expression with which this type of play is labelled presents, in the common sense, a semantic aura that refers to a series of terms with a negative meaning such as falsehood, deception, error, illusion. Starting from the assumption that the understanding of the meaning of pretend play must be based on a distancing from the idea of truth as a reflection of reality, I’ll present and discuss some play theories which show, on the contrary, the necessity and the productivity of the “as if.” In line with this perspective, infantile pretend play will be considered as the prototype of an essential human experience to which particular attention should be paid, to be promoted with sensitivity and delicacy, and not to be used improperly as an instructional tool.